Hero Archetype in Passing Euphoria Wattpad Story - Anisa Dinda Noviyanti; E. Ngestirosa Endang Woro Kasih (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
Wattpad is currently not only a medium for entertainment, but has also developed as a place to convey social values, including the representation of heroic characters. One of the prominent stories is Passing Euphoria (2021), which contains characters with heroic roles that are relevant to analyze using a psychological approach. Understanding how heroes are represented in popular fiction works such as Wattpad is important to see how heroic values are constructed in today's popular culture which will be beneficial for future research in using popular fiction works for individuals who want to investigate hero archetypes. This analysis also aims to uncover the representation of heroes through a qualitative descriptive approach and hero archetype theory. Three archetypes out of twelve hero archetypes were found. They are The Innocent, Caregiver, and Warrior. This research is a descriptive qualitative research conducted by describing data obtained from quotes, dialog, and narratives to represent heroes. This research uses Carol S. Pearson's hero archetype theory. The results showed that the wattpad story Passing Euphoria (2021) depicts the hero as a strong figure, able to overcome all situations with their strength because they are optimistic and believe in their strength. This story emphasizes the importance of believing in yourself to be able to overcome all problems.